2019
DOI: 10.1186/s10397-019-1065-9
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of deeply infiltrating endometriosis - 7 year experience in a tertiary endometriosis centre in London

Abstract: Background: Deeply infiltrating endometriosis has an estimated prevalence of 1% in women of reproductive age. Ninety percent have rectovaginal lesions but disease may also include the bowel, bladder and ureters. Current practice often favours minimally invasive surgical excision; however, there is increasing evidence that medical management can be as effective as long as obstructive uropathy and bowel stenosis are excluded. Our objective was to establish the proportion of women with deeply infiltrating endomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…7 Medical management was not efficacious in our patients as elicited by the clinical history, which corresponded with the findings of other studies in the literature. 19 Moreover, prolonged and unguided medical management may lead to tissue fibrosis which further makes the surgery technically demanding. Some of the review articles have documented the role of imaging in the pre-operative diagnosis, but no definite features suggestive of vault endometriosis has been specified.…”
Section: Resultsmentioning
confidence: 99%
“…7 Medical management was not efficacious in our patients as elicited by the clinical history, which corresponded with the findings of other studies in the literature. 19 Moreover, prolonged and unguided medical management may lead to tissue fibrosis which further makes the surgery technically demanding. Some of the review articles have documented the role of imaging in the pre-operative diagnosis, but no definite features suggestive of vault endometriosis has been specified.…”
Section: Resultsmentioning
confidence: 99%
“…In uncomplicated cases, medications that downregulate estrogen levels, such as oral contraceptive pills, gonadotropin-releasing hormone agonists, danazol, or progestins, have been shown to improve quality of life. 8 In severe cases where patients fail hormonal treatment or in patients who no longer want children but are of reproductive age, a total hysterectomy with bilateral oophorectomy may be preferred, 9 particularly if they present with complications such as severe bleeding, bowel obstruction, or concern for malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…7 It has been shown that quality of life is comparable with medical and surgical treatment. 8 Nonetheless, only invasive treatments can fully eradicate the endometrial foci. In uncomplicated cases, medications that downregulate estrogen levels, such as oral contraceptive pills, gonadotropin-releasing hormone agonists, danazol, or progestins, have been shown to improve quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of endometriosis is dependent on the severity of the disease. Studies show that patient quality of life and satisfaction rates are comparable with medical and surgical treatment [17]. Medication treatment offers success in early uncomplicated cases and includes oral contraceptive pills, progestins, danazol, and gonadotropin-releasing hormone (GnRH) agonists.…”
Section: Discussionmentioning
confidence: 99%